Entwicklung der Erreichbarkeit der Schweizer Gemeinden: 1950 bis 2000 - Fröhlich, Philipp; Tschopp, Martin; Axhausen, Kay W. (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The accessibility of the Swiss municipalities has changed substantially in the last 50 years due to the extension of the road network, improvements of the public transport and population growth. The paper deals with the first two variables and the resulting changes. The ratio of road-based to public transport-based accessibility has changed little over the time period from 1950 to 2000 in Switzerland.